Hubungan Siklus Menstruasi, Kualitas Tidur, dan Pengetahuan Siswi dengan Kejadian Anemia di MTs. Negeri 2 Lombok Tengah - Suci Nirmala; Rosalina Yolanda; Rizki Mulianti; Dany Karmila (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Anemia is a condition where the number of red blood cells in the body is lower than the normal number. Anemia is a health problem that has a fairly high incidence rate throughout the world. This study aims to determine the relationship between the menstrual cycle, sleep quality and knowledge of female students with the incidence of anemia in MTs. Negeri 2 Central Lombok. This research is an analytical observational study using a cross sectional design. The sampling technique uses a probability sampling technique, namely simple random sampling. The research sample was 100 samples with each sample meeting the inclusion and exclusion criteria. The data obtained were analyzed using the chi-square correlation test. The results of this research showed that 48% of respondents had abnormal menstrual cycles and 52% had normal menstrual cycles. 40% of respondents had poor sleep quality and 60% had good sleep quality. Respondents had poor knowledge as much as 33%, sufficient knowledge as much as 44% and good knowledge as much as 23%. There is a relationship between the menstrual cycle and the incidence of anemia with a p-value of 0.000 and OR 32.143. There is a relationship between sleep quality and the incidence of anemia with a p-value of 0.000 and OR 20.487. There is a relationship between female students' knowledge and the incidence of anemia with a p-value of 0.000 and OR 15.882. There is a significant relationship between the menstrual cycle, sleep quality and knowledge of female students with the incidence of anemia in MTs. Negeri 2 Central Lombok.